Foliar fungal communities in agroecosystems depend on crop identity and neighboring vegetation - Whitaker, B. K.; Heiniger, R. W.; Hawkes, C. V. (Frontiers in Microbiomes, 2023)
Agricultural intensification causes plant diversity loss and environmental homogenization, which may result in changes to plant-microbiome interactions mediating plant growth and stress tolerance. We hypothesized that foliar fungal microbiomes would depend on plant traits and environmental filters, constrained by neighboring vegetation expected to serve as a fungal source. Thus, we sampled foliar fungi from four crops (three annual and one perennial), four sites per crop, and three varieties per annual crop, across a 500-km expanse in North Carolina, USA and tested the role of host traits, environmental traits, and vegetative landcover on foliar fungal community structure. Crop species and site were major determinants of community structure, primarily due to differences in plant size and growing season. Site consistently explained 10x more variation in community structure than host variety across the annual crops. Finally, reduced natural vegetative cover surrounding farms was correlated with decreased fungal richness and more homogeneous microbiome assembly. Based on these results, we posit that foliar fungal assembly in crops results from host and environmental filters acting on inputs from the nearby vegetation. Future efforts at agricultural microbiome management must therefore consider landscape management and will require an improved understanding of how agricultural intensification alters microbial source pools.